The Concept of Children's Education Perspective of Ibn Qayyim al-Jauziyyah - Ihsan Pratama, Arizqi; Saefuddin, Didin; Husaini, Adian; Indra, Hasbi (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
Children's education consciously guides and guides the condition of the soul, especially so that it can cultivate good morals and habits from the beginning of its growth and development, until it reaches puberty, so that a personality is formed in accordance with educational goals. In order to study the concept of children's education, it is necessary to study the thoughts of previous scholars, because it is undeniable that there have been many contributions made by previous scholars, especially in the world of education. Educational figures who are used as research objects are scholars of interpretation, hadith, ushuluddin, and Arabic, but not much research has been done on the concept of education. The concept of the figure's education is outlined in his books, but the world of education does not recognize him as an educational figure. Ibn Qayyim Al-Jauziyyah, with his characteristics and personality as a knowledgeable person, we will undoubtedly find some hints, views and instructions about education, in addition to his sincerity in discussing various other fields of knowledge. We certainly find advice about the concept of education in the books written by these figures. Therefore it is very interesting if it is discussed more deeply regarding the concept of children's education according to Ibn Qayyim Al-Jauziyyah. The type of research used in collecting data is library research, namely a series of activities related to library data collection methods, reading and recording and processing research materials. There are three important aspects in the concept of children's education according to Ibn Qayyim al-Jauziyyah, namely the goals of children's education, children's education materials, and educational methods. In terms of children's education goals, Ibn Qayyim al-Jauziyyah explained that the main goal of Islamic education is to grow and develop all of the child's potential, maintain nature, and protect it from deviations and realize the meaning of worship to Allah. In the aspect of children's education material, Ibnu Qayyim revealed that there are seven children's education materials namely Faith Education, Mental Education, Intellect Education, Moral Education, Social Education, Physical Education and Sex Education. In terms of educational methods, Ibn Qayyim explained several methods that can be used in children's education including the habituation method, the exemplary method, the advice method, and the punishment method.